Dealing with diversity in Muslim schools in Britain - Lahmar, Fella (2012)
This research was designed to explore the ways that Muslim schools are dealing with the tensions arising from the diversity presented to them within their own religious group and how this then shapes individual schools as they operate within a post 9/11 and 7/7 social context.